Can Faces Prime a Language?. (September 2015) - Woumans, Evy; Martin, Clara D.; Vanden Bulcke, Charlotte; Van Assche, Eva; Costa, Albert; Hartsuiker, Robert J.; Duyck, Wouter
Bilinguals have two languages that are activated in parallel. During speech production, one of these languages must be selected on the basis of some cue. The present study investigated whether the face of an interlocutor can serve as such a cue. Spanish-Catalan and Dutch-French bilinguals were first familiarized with certain faces, each of which was associated with only one language, during simulated Skype conversations. Afterward, these participants performed a language production task in which they generated words associated with the words produced by familiar and unfamiliar faces displayed on-screen. When responding to familiar faces, participants produced words faster if the faces were speaking the same language as in the previous Skype simulation than if the same faces were speaking a different language. Furthermore, this language priming effect disappeared when it became clear that the interlocutors were actually bilingual. These findings suggest that faces can prime a language, but their cuing effect disappears when it turns out that they are unreliable as language cues.